Upper motor neuron evaluation in multiple sclerosis patients treated with Sativex®. (8th August 2016) - Carotenuto, A.; Iodice, R.; Petracca, M.; Inglese, M.; Cerillo, I.; Cocozza, S.; Saiote, C.; Brunetti, A.; Tedeschi, E.; Manganelli, F.; Orefice, G.
Abstract: Background: Spasticity in multiple sclerosis (MS) results from an imbalance of inputs from descending pathways to the spinal motor circuits, as well as from a damage of the corticospinal tract (CST). Objectives: To assess CST impairment in MS patients with and without spasticity and to evaluate its evolution under Sativex ® treatment. Methods: Ten MS patients with spasticity ("cases") underwent clinical (EDSS, 9‐hole Peg, Ashworth scale, Timed 25‐Foot Walk, and NRS for spasticity), MRI (CST fractional anisotropy [FA]), and electrophysiological (central motor conduction time [CMCT] and H/M ratio) evaluations at baseline and after 12 months. We selected 20 MS patients without spasticity as control group at baseline. Results: At baseline, cases showed a lower CST FA (0.492±0.045 vs 0.543±0.047; P =.01) and a higher CMCT ( P =.001) compared to the control group. No correlations were found between clinical, electrophysiological, and MRI features. After 12 months, cases showed a decrease in non‐prevalent degree of impairment (PDI) side FA (0.502±0.023 vs 0.516±0.033; P =.01) without differences for electrophysiological features compared to baseline. Treatment with Sativex ® resulted in a reduction of NRS for spasticity ( P =.01). Conclusions: We confirm the presence of CST impairment in MS patients with spasticity. We did not identify structural/electrophysiological correlates that could explain Sativex ® clinical effect.